Організація провінційного управління Османської імперії XVI ст. за даними канун-наме - Ковальчук, М. (Український історичний збірник, 2017)
У статті на основі даних султанських канун-наме розглядається організація провінційного управління Османської імперії у XVI ст. Зазначається, що систему влади на місцях формували представники військово-адміністративної, судової та фінансової ліній османського управління, головним завданням яких було налагодження і зміцнення зв'язків між провінцією та центром. In the article the organization of the provincial administration of the Ottoman Empire in the XVI century is considered according to the sultans’ kanunname. The author analyses the administrative divisions of the Ottoman Empire: the largest ottoman provincies — eyalets divided into two types: timarli, in which the system of sanjaks, ottoman law, timar system were established; and salyaneli, where timar system was absent, all taxes were gathered and distributed to local needs; the secondorder administrative-military territorial units were sanjaks, the subdivisions of sanjak were kazas and kadiluks, then — nahiyes. Also, she marks that outside this system were various types of vassal and tributary states. The governance of large territory, control over the execution of orders, establishment of relations between different groups of multi-ethnic population of the empire, which lived mostly not in the metropolitan area, but in the provinces, needed the constant functioning of local authorities. The author notes that the system of local authorities was formed by representatives of the military-administrative (sipahi-timarli, sanjakbey, beylerbey, the Grand Vizier), judicial (qadis (judges), kazaskers, sheikh-ul-Islam) and financial (defterdars) lines of the Ottoman government, whose main task was to organize and strengthen the communications between the province and the center. Special attention is given to the description of the place and role, rights and duties of beylerbey, sanjakbey, qadi (judge), defterdar and other local managers at the system of the ottoman provincial administration.